Primary antibody response after influenza virus infection is first dominated by low-mutated HA-stem antibodies followed by higher-mutated HA-head antibodies - Aartse, Aafke; Mortier, Daniella; Mooij, Petra; Hofman, Sam; van Haaren, Marlies M.; Corcoran, Martin; Karlsson Hedestam, Gunilla B.; Eggink, Dirk; Claireaux, Mathieu; Bogers, Willy M. J. M.; van Gils, Marit J.; Koopman, Gerrit (Frontiers in Immunology, 2022)
Several studies have shown that the first encounter with influenza virus shapes the immune response to future infections or vaccinations. However, a detailed analysis of the primary antibody response is lacking as this is difficult to study in humans. It is therefore not known what the frequency and dynamics of the strain-specific hemagglutinin (HA) head- and stem-directed antibody responses are directly after primary influenza virus infection. Here, sera of twelve H1N1pdm2009 influenza virus-infected cynomolgus macaques were evaluated for HA-head and HA-stem domain antibody responses. We observed an early induction of HA-stem antibody responses, which was already decreased by day 56. In contrast, responses against the HA-head domain were low early after infection and increased at later timepoint. The HA-specific B cell repertoires in each animal showed diverse VH-gene usage with preferred VH-gene and JH-gene family usage for HA-head or HA-stem B cells but a highly diverse allelic variation within the VH-usage. HA-head B cells had shorter CDRH3s and higher VH-gene somatic hyper mutation levels relative to HA-stem B cells. In conclusion, our data suggest that HA-stem antibodies are the first to react to the infection while HA-head antibodies show a delayed response, but a greater propensity to enter the germinal center and undergo affinity maturation.